2012
DOI: 10.1007/s13632-012-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

TTP Curves and Microstructural Evolution Mechanism After Quenching in Aluminum Alloy 6082

Abstract: Temperature-time-property (TTP) curves for aluminum alloy 6082 were acquired by an interrupted quenching method. The TTP curves presented a ''C''-shape and the critical temperature range was 240-440°C with temperature at the nose of the C-curve of approximately 335°C. At this temperature, the greatest rate of second phase development and the largest, and most rapid, drop in hardness was observed. The change was approximately 50% of the maximum when isothermally held or 50 s. Microstructural evolution of the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…By this, the production of components with locally adapted mechanical properties is possible. Investigations by Gao et al revealed, that the alloy AA6082 has a critical cooling range between 240 °C and 440 °C [8]. Studies by Sajadifar et al demonstrated that various cooling rates can be obtained by adjusting the tool temperature [9].…”
Section: Production Of Aluminum Components With Tailored Mechanical P...mentioning
confidence: 99%
“…By this, the production of components with locally adapted mechanical properties is possible. Investigations by Gao et al revealed, that the alloy AA6082 has a critical cooling range between 240 °C and 440 °C [8]. Studies by Sajadifar et al demonstrated that various cooling rates can be obtained by adjusting the tool temperature [9].…”
Section: Production Of Aluminum Components With Tailored Mechanical P...mentioning
confidence: 99%
“…Depending on the region in the SZ, they underwent dissolution (Figure 5c); however, in some, coarser precipitates were observed (Figure 5d). Based on the literature analysis, they can be assumed to be β' (rods) and β (plates) [34,35], which contributed to the strengthening being lower in comparison to the β″ precipitates. Between the welds, two main differences were observed.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…From these results, it was evident that the stability of supersaturated solid solution in Ge-bearing was enhanced as compared to the based alloy. It was pointed out that the incubation period represented the stability of the supersaturated solid solution [16], i.e. higher stability of the solid solution equaled to a longer incubation period.…”
Section: Temperature-time-property Curvesmentioning
confidence: 99%